Comparing starting antiretroviral therapy for hiv before pregnancy versus during pregnancy as a risk factor associated to poor neonatal outcomes in a regional reference hospital in trujillo in 2015-2023 - Caciano Leiva, Roger Berardo (2024)
Objective: To determine whether pre-conception initiation of antiretroviral (ARV) therapy compared to pregnancy ARV initiation is a risk factor for adverse neonatal outcomes in women more than 18 years old in Belen Hospital in Trujillo (BHT). Material and Methods: This is an analytical observational study performed in a retrospective cohort. Sample size was 168 pregnant women diagnosed with HIV infection and receiving antiretroviral (ARV) therapy, who were divided in two groups: 84 women who started ARV prior to conception and 84 who started ARV after conception. The analysis was performed using the Chi-square test and relative risk (RR) was calculated, with 95% confidence intervals (CI) and 5% significance. Results: The rate of adverse neonatal outcomes was 48.8% in women starting ARV after conception and 21.4% in those who started ARV after conception, and this difference was significant (p<0.001). Adverse neonatal outcomes, such as low birthweight (p= 0.015) and being small for gestational age (p= 0.035) were significantly associated with ARV initiation before pregnancy. Conclusion: ARV initiation before pregnancy seems to be associated with adverse neonatal outcomes when compared with ARV initiation during pregnancy, although this may be adjusted for potential confounding factors.